2023
DOI: 10.3390/healthcare11142029
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Associated Factors of Academic Stress among Medical Students of King Khalid University: An Analytical Cross-Sectional Study

Abstract: Medical students are the category of academic population with the highest levels of stress. This study aimed to assess the prevalence of academic stress among medical students in Saudi Arabia and to identify its associated factors. This cross-sectional study was conducted at the College of Medicine at King Khalid University, Abha. The Medical Student Stressor Questionnaire (MSSQ) was used to evaluate the stress caused by different factors. A total of 422 medical students participated in this study. Among the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Our findings support previous research that found stress factors in students: academic, teaching, and learning-related stressors [11]. The same topics were detected in our research and are shown in Figure 13.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings support previous research that found stress factors in students: academic, teaching, and learning-related stressors [11]. The same topics were detected in our research and are shown in Figure 13.…”
Section: Discussionsupporting
confidence: 93%
“…We challenge the findings of [11], asserting that lowergrade students experience more stress than sixth-year medical students. Our research findings indicate that students in higher grades, specifically those pursuing Master's degrees (the same age as medical students in the 5th-6th grades), demonstrate the highest stress levels.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, academic burnout has become a relevant factor affecting college students' mental health. Although high levels of burnout are common among university students, medical students are particularly vulnerable because of the persistent exposure to specific risk factors, such as the caring of people suffering from different disorders, and the high competitiveness in medical school [99,100]. In particular, the tough competition among medical students could probably be considered as a motivational drive that is helpful in overcoming the several obstacles of the training curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Bughi et al (2006) conducted research in California involving 104 students and found that the prevalence of stress in medical students was 51%. Research in Mansoura, Saudi Arabia, which showed that 94.5% of medical students experienced stress (Al-Shahrani et al, 2023). Research conducted in Thailand by Saipanish (2003) involving 686 students showed that 61.4% of medical students experienced stress.…”
Section: Introductionmentioning
confidence: 99%